2006
DOI: 10.1111/j.1468-2451.2006.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Local products and geographical indications: taking account of local knowledge and biodiversity

Abstract: The debate and negotiations in progress at the international level concerning the protection of geographical indications (GI) are of direct interest to the local agricultural products and foodstuffs called terroir products. Beyond the protection of the use of their name, which is the founding principle of this system, and the legal and economic considerations this system implies, new questions are being raised about these products concerning the diversification of farming and sustainable development. More and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 6 publications
0
72
0
11
Order By: Relevance
“…An awareness-building path over cultural heritage and its productive potentialities is launched by a research team from the DiARC, Federico II, (Progetto Prin 2010 -11) to promote new perspectives towards technological transitions, based on identity and inclusiveness. The basis of the approach is that the collective re-appropriation of knowledge and memories can contribute to activating a gradual process of individual and collective empowerment (Bérard, Marchenay, 2006). The design perspective fits into a cultural framework marked by the European Landscape Convention (Council of Europe, 2000).…”
Section: Thesis Statementmentioning
confidence: 99%
“…An awareness-building path over cultural heritage and its productive potentialities is launched by a research team from the DiARC, Federico II, (Progetto Prin 2010 -11) to promote new perspectives towards technological transitions, based on identity and inclusiveness. The basis of the approach is that the collective re-appropriation of knowledge and memories can contribute to activating a gradual process of individual and collective empowerment (Bérard, Marchenay, 2006). The design perspective fits into a cultural framework marked by the European Landscape Convention (Council of Europe, 2000).…”
Section: Thesis Statementmentioning
confidence: 99%
“…The legislative framework adopted by the EU and that is currently in force [Regulation (EU) No 1151/2012; European Comission, 2012b] provides that producers apply for the GI protection. They are required to submit an application accompanied by product specifications that contain rules for the production process and the area within which the product is produced, thus linking the agri-food production with specific rural culture and local geographical aspects in the definition of terroir (Bérard and Marchenay, 2006). Once again, the wine sector followed a different piece of legislation and its integration within the same legislative scheme as per other agri-food products occurred with Regulation (CE) No 479/2008(European Comission, 2008.…”
Section: Methodsmentioning
confidence: 99%
“…Although environmental protection is not explicitly addressed either in EU legislation or in national requirements for the protection of geographical indica-tions, several studies reported their general favourable effect. An overall capacity was observed to maintain multifunctional agricultural systems (Belletti et al, 2003), landscapes and biodiversity thanks to the protection of small-scale production and conservation of local ecosystems (Bérard and Marchenay, 2006). However, some weaknesses were also highlighted, such as the risk of favouring genetic erosion in plant varieties and animal breeds (Thévenod-Mottet, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The geographic locations are sometimes also known for their unique pedo-climate conditions also referred to as "terroir" analogous to wine regions (Rotaru, Filipov, Mustea, & Stoleru, 2010). The product-based farming system should also be known in the defined geographical terroir (Berard & Marchenay, 2006). Such holistic conceptualisation of terroir has never been attempted so far in the coffee-based farming system and therefore we need to develop it.…”
Section: Challenges In Zoning Coffee Terroirsmentioning
confidence: 99%
“…Bowen & Zapata, 2009;Vaudour, 2002), for mainly wine (e.g. Berard & Marchenay, 2006;Foroni et al, 2017;Rotaru et al, 2010) and olive oil (Belletti, Marescotti, Sanz-Cañada, et al, 2015). Some terroirs are found outside Europe, such as the example of Taquila cheese in Mexico (S. Bowen, 2010;S.…”
Section: Introductionmentioning
confidence: 99%